An approach of total endoscopic atrial myxoma resection without robotic assistance - Wang, Xingming; Ma, Shuai; Ma, Bingbing; Sun, Hourong; Wang, Biao; Liu, Kai; Ma, Zengshan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundConventional surgery presents significant challenges for elderly patients with atrial myxoma and ascending aorta calcification. This study aims to evaluate the feasibility and safety of total thoracoscopic resection of atrial myxoma.MethodsA total of 83 patients who underwent totally thoracoscopic resection of atrial myxoma between January 2013 and April 2024 were retrospectively analyzed. Three 1.0–2.0-cm thoracic incisions were made in the right chest, and all procedures were conducted under totally thoracoscopy. Right atrial myxomas were resected via a right atrium approach, while left atrial myxomas were removed through an interatrial groove approach. For the 46 patients with ascending aortic plaque or calcification, the operations were performed on the beating heart without aortic cross-clamping.ResultsThe totally thoracoscopic resection of atrial myxoma was successfully performed in all patients without in-hospital mortality or a switch to the sternotomy approach. The duration of operation, CPB time, and aortic cross-clamp time in the beating-heart group were shorter than in the arrested-heart group. There were no statistically significant differences between the groups in mechanical ventilation time, duration of ICU, postoperative hospital stay, and postoperative 24-h drainage volume. The rate of tracheal extraction in the operating room was higher in the beating-heart group than that in the arrested-heart group. None of the patients required a blood transfusion or experienced serious complications.ConclusionTotal thoracoscopic resection is a feasible and safe method for addressing atrial myxomas, particularly in elderly patients with ascending aortic calcification and persistent cardiac failure.